Deter and Deny Strategies in Counter Terrorism Crime - Masyhar, Ali (Law Research Review Quarterly, 2017)
ADULTS, movement and human traffic are not only confined around one country alone. In a very short time, a person can move from one country to another, even moving to several countries. Such conditions, of course, must be followed by a renewal of the concept of law, mainly related to criminal law. Crime also moves not only struggling in one area of ​​the country, but has crossed national borders. One of the crimes that goes beyond national borders is terrorism. Terrorism is one form of crime that has the potential to be strong across national borders (transnational crime) and even organized (transnational organized crime), because it networking with organized groups that reside in other countries. Therefore, in order to anticipate terrorism that has international networks, the concept of Cekal (Prevent-Tangkal) becomes a very telling instrument. Prevention is a temporary ban on people leaving Indonesia based on immigration reasons or other reasons determined by law. Meanwhile, deterrence is a prohibition against foreigners entering Indonesian territory based on immigration reasons